THE PROBLEM OF TRUTH IN ANCIENT PHILOSOPHY - Suhrob Panjiyev (American Journals, 2023)
The article analyzes the views on truth of ancient Western philosophers such as Plato, Aristotle, Democritus, Heraclitus and Zeno, and discusses the importance of dogmatic and skeptical ideas in revealing the content and concept of truth.
Keywords: Ancient period, truth, problem of truth, concept of truth, practice, dogmatism, rationalism, empiricism, skepticism